P4B533-X Motherboard : Intel 845 E Chipset series support CD Rev.70.01 - P4B533... (ASUStek Computer Inc., 2003)
Besar file 200 MB, berisi file: Bin, Drivers (audio, chipset, lan, USB2), Software (acrobat, afudos, asusupdt, directX, logo, pccillin, probe, screensaver).